Enantioselective and Diastereodivergent Access to α‐Substituted α‐Amino Acids via Dual Iridium and Copper Catalysis. Issue 5 (23rd January 2019) - Zhang, Jiacheng; Huo, Xiaohong; Li, Bowen; Chen, Zhouli; Zou, Yashi; Sun, Zhenliang; Zhang, Wanbin
Abstract: The work reported within this paper describes an example of the application of bimetallic catalysts system in allylic substitution reactions. The development of new nucleophiles and the control of enantio‐ and diastereoselectivity are the main research topics in this area. An improvement in the reactivity and diastereoselectivity has been realized for the dual Ir/Cu catalyzed allylic alkylation of inactive prochiral nucleophiles, under mild reaction conditions. Furthermore, the choice of the metallacyclic iridium complex and chiral Cu‐Phox complex combination allows for access to all four stereoisomers from the same starting materials with excellent enantioselectivity and diastereoselectivity (up to >99% ee and >20:1 dr). Significantly, this method provides a stereodivergent access to 2‐amino‐3‐methylpent‐4‐acid ester, an important fragment for the synthesis of Halipeptin A. Abstract :